Titanium oxide-containing powder and manufacturing method of titanium oxide-containing powder

A method for producing titanium oxide-containing powder with a balanced dielectric constant and loss tangent is achieved by preparing a slurry with specific particle sizes and firing at low temperatures, addressing the challenge of mixing with resin materials while preserving dielectric properties.

JP2025009877APending Publication Date: 2025-01-20SAKAI CHEM IND CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024088819
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-07-03
Filing Date
2024-05-31
Publication Date
2025-01-20

AI Technical Summary

Technical Problem

Existing methods for producing titanium oxide powders for high-frequency circuit boards fail to achieve a balance between excellent dielectric properties and suitable particle size for mixing with resin materials, leading to deteriorated dielectric properties during pulverization.

Method used

A method involving the preparation of a slurry with titanium oxide secondary particles of 0.1 to 4 μm, granulation, and firing at 1100°C or less to produce a titanium oxide-containing powder with a dielectric constant of 14 or more and a dielectric loss tangent of 0.006 or less, optionally incorporating calcium titanate to enhance properties.

Benefits of technology

The resulting powder exhibits high dielectric constant and low dielectric loss tangent, suitable for mixing with resin materials, maintaining excellent dielectric properties and facilitating uniform mixing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025009877000004
    Figure 2025009877000004
  • Figure 2025009877000005
    Figure 2025009877000005
  • Figure 2025009877000006
    Figure 2025009877000006
Patent Text Reader

Abstract

To provide a dielectric material having excellent dielectric property and a particle size suitable for blending with a resin material in good balance.SOLUTION: A titanium oxide-containing powder is a powder containing titanium oxide. The powder is characterized by that a permittivity at 10 GHz is 14 or over, a dielectric tangent is 0.006 or under, and a specific surface area is 4-16 m2 / g.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a titanium oxide-containing powder and a method for producing the titanium oxide-containing powder. [Background technology]

[0002] With recent advances in information and communication technology, there is a demand for smaller, lighter, and faster communication devices. Furthermore, to enable the communication of larger volumes of information, radio waves in the GHz frequency range are now being used. In order to miniaturize communication devices compatible with high frequency bands, it is necessary to use circuit board materials with excellent high frequency transmission characteristics (low dielectric loss). Dielectric loss is proportional to the product of the frequency, the dielectric constant (ε or Dk) and the dielectric tangent (tan δ or Df) of the circuit board, so in order to reduce dielectric loss, it is necessary to reduce the dielectric tangent of the board. Furthermore, within the board, the wavelength of the electromagnetic wave is 1 / (ε) 1 / 2 Therefore, the larger ε is, the more compact the circuit board can be. Therefore, materials with high dielectric constant and low dielectric tangent are required for circuit boards of small devices used in high frequency bands.

[0003] Substrate materials with the above dielectric properties include inorganic dielectric materials such as titanium oxide and titanates, and organic fluororesins. Of these, substrates made of dielectric materials are excellent in ε and tan δ but have problems with processability, while substrates made of resin are excellent in moldability, processability and tan δ but have a small ε. For this reason, in order to obtain a substrate that has the advantages of both, composite substrates have been proposed in which a dielectric material is mixed into a resin material. The above-mentioned dielectric material is obtained by reducing the specific surface area of ​​titanates, which exhibit excellent dielectric properties, through high-temperature firing or a special method. However, since particle aggregation occurs during the specific surface area reduction process, it is necessary to pulverize the aggregated particles generated by the specific surface area reduction process to adjust them to an appropriate particle size in order to mix the dielectric material into the composite substrate. The fine particles generated by pulverization tend to be difficult to knead into the resin due to their high specific surface area, and the remaining coarse particles cause the surface roughness of the composite substrate after the dielectric material is mixed in to increase. To address this issue, a method of adjusting the particle size to an appropriate size by pulverization for filling into the resin, and a method of carrying out both the firing and pulverization processes multiple times to suppress the deterioration of the dielectric properties and fluidity due to pulverization have been disclosed (see Patent Documents 1 and 2). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent No. 5727224 [Patent Document 2] JP 2005-174711 A Summary of the Invention [Problem to be solved by the invention]

[0005] As mentioned above, conventionally, agglomerated particles generated during the specific surface area reduction treatment of dielectric materials are pulverized to an appropriate particle size and then mixed with a resin material to manufacture a composite substrate, but pulverization of agglomerated particles deteriorates the dielectric properties of the dielectric material. For this reason, titanium oxide that combines excellent dielectric properties with a particle size suitable for mixing with resin materials has not yet been obtained.

[0006] In view of the above-mentioned current situation, an object of the present invention is to provide a dielectric material that combines excellent dielectric properties with a particle size suitable for mixing into a resin material. [Means for solving the problem]

[0007] The present inventors have investigated dielectric materials that combine excellent dielectric properties with a particle size suitable for mixing with resin materials, and have discovered that by preparing a slurry containing titanium oxide having an average secondary particle size of 0.1 to 4 μm and a solvent, obtaining granulated particles from the obtained slurry, and firing the obtained particles at a temperature of 1100° C. or less, a titanium oxide-containing powder that combines excellent dielectric properties with a particle size suitable for mixing with resin materials can be obtained, thereby completing the present invention.

[0008] That is, the present invention is as follows. [1] A powder containing titanium dioxide, The powder has a dielectric constant of 14 or more at 10 GHz, a dielectric dissipation factor of 0.006 or less, and a specific surface area of ​​4 to 16 m 2 / g of the titanium oxide-containing powder.

[0009] [2] The titanium oxide-containing powder according to [1], further comprising calcium titanate.

[0010] [3] The titanium dioxide-containing powder according to [1] or [2], characterized in that the average particle size is 0.1 to 100 μm.

[0011] [4] A resin composition comprising the titanium oxide-containing powder according to any one of [1] to [3] and a resin.

[0012] [5] A method for producing a titanium oxide-containing powder, comprising the steps of: The production method includes a first step of preparing a slurry containing titanium oxide having an average secondary particle size of 0.1 to 4 μm and a solvent; A second step of obtaining granulated particles from the slurry obtained in the first step; and a third step of sintering the particles obtained in the second step at a temperature of 1100°C or less. 2. The method for producing a titanium oxide-containing powder comprising the steps of:

[0013] [6] The method for producing a titanium oxide-containing powder according to [5], wherein the first step is a step of preparing a slurry containing titanium oxide having an average secondary particle size of 0.1 to 4 μm, a calcium-containing compound, and a solvent.

[0014] [7] The method for producing a titanium oxide-containing powder according to [6], characterized in that the calcium-containing compound is at least one selected from the group consisting of calcium carbonate, calcium acetate, calcium nitrate, calcium oxalate, calcium bicarbonate, and calcium titanate.

[0015] [8] The method for producing a titanium oxide-containing powder according to any one of [5] to [7], wherein the second step is carried out by spray drying the slurry. Effect of the Invention

[0016] The titanium oxide-containing powder of the present invention has excellent dielectric properties and a particle size suitable for mixing with resin materials, and therefore can be suitably used as a dielectric material to be mixed with a resin. The method for producing a titanium oxide-containing powder of the present invention is a method for producing such a titanium oxide-containing powder. [Brief description of the drawings]

[0017] [Figure 1] FIG. 1 shows various analytical data for calculating the circularity of the titanium oxide-containing powder obtained in Example 11. [Diagram 2] FIG. 1 shows various analytical data for calculating the circularity of the titanium oxide-containing powder obtained in Comparative Example 3. [Diagram 3] FIG. 2 is a graph showing the results of particle size distribution measurement of the titanium oxide-containing powder obtained in Example 1. [Figure 4] FIG. 2 is a photograph showing the results of SEM observation of the titanium oxide-containing powder obtained in Example 1. [Figure 5-1] FIG. 2 is a photograph showing the results of SEM-EDS measurement of the titanium oxide-containing powder obtained in Example 1. [Figure 5-2] FIG. 2 is a diagram showing a spectrum of the results of SEM-EDS measurement of the titanium oxide-containing powder obtained in Example 1. [Figure 6] FIG. 2 is a diagram showing the results of XRD measurement of the titanium oxide-containing powder obtained in Example 1. [Figure 7] FIG. 1 shows the results of particle size distribution measurement of the titanium oxide-containing powder obtained in Example 11. [Figure 8] FIG. 1 is a photograph showing the results of SEM observation of the titanium oxide-containing powder obtained in Example 11. [Figure 9-1] FIG. 1 is a photograph showing the results of SEM-EDS measurement of the titanium oxide-containing powder obtained in Example 11. [Figure 9-2] FIG. 13 is a diagram showing a spectrum of the results of SEM-EDS measurement of the titanium oxide-containing powder obtained in Example 11. [Figure 10] FIG. 1 shows the results of XRD measurement of the titanium oxide-containing powder obtained in Example 11. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] A preferred embodiment of the present invention will be described in detail below, but the present invention is not limited to the following description, and can be modified and applied as appropriate within the scope that does not change the gist of the present invention.

[0019] 1. Titanium oxide-containing powder The titanium oxide-containing powder of the present invention has a dielectric constant of 14 or more at 10 GHz, a dielectric dissipation factor of 0.006 or less, and a specific surface area of ​​4 to 16 m 2 The titanium oxide-containing powder having such a high dielectric constant and low dielectric tangent can be suitably used as a material for circuit boards of communication devices and the like used in high frequency bands. The dielectric constant of the titanium oxide-containing powder at 10 GHz may be 14 or more, but is preferably 16 or more, more preferably 18 or more, and even more preferably 20 or more. There is no particular upper limit to the dielectric constant of the titanium oxide-containing powder, but it is usually 30 or less. The titanium oxide-containing powder may have a dielectric loss tangent at 10 GHz of 0.006 or less, preferably 0.004 or less, and more preferably 0.003 or less. There is no particular lower limit to the dielectric loss tangent of the titanium oxide-containing powder, but it is usually 0.0001 or more. The dielectric constant and dielectric loss tangent of the titanium oxide-containing powder can be measured by the method described in the Examples below.

[0020] The titanium oxide-containing powder of the present invention has a specific surface area of ​​4 to 16 m 2 / g, which makes it suitable for mixing with resin materials. However, the specific surface area of ​​titanium oxide-containing powder is 4 to 14 m 2 / g. More preferably, it is 5 to 12 m 2 / g, and more preferably 5 to 10 m 2 / g, and particularly preferably 6 to 8m 2 / g. The specific surface area of ​​the titanium oxide-containing powder can be measured by the method described in the Examples below.

[0021] The titanium oxide-containing powder of the present invention may contain titanium oxide, and may or may not contain other components, but preferably further contains calcium titanate.As described below, by using a calcium-containing compound when producing a titanium oxide-containing powder, the titanium oxide-containing powder obtained becomes spherical particles with a smoother surface, which is easier to mix uniformly with resin.And by using a calcium-containing compound when producing a titanium oxide-containing powder, the titanium oxide-containing powder obtained contains calcium titanate. When calcium titanate is contained, the content is preferably 1 to 90 mass% relative to 100 mass% of the titanium oxide-containing powder as a whole, more preferably 2.5 to 70 mass%, further preferably 5 to 60 mass%, and particularly preferably 5 to 35 mass%.

[0022] When the titanium oxide-containing powder of the present invention contains titanium oxide and calcium titanate, it preferably contains composite particles of titanium oxide and calcium titanate. By containing such composite particles, the titanium oxide-containing powder becomes a material with a higher dielectric constant and a lower dielectric tangent.

[0023] The particle size of the titanium oxide-containing powder of the present invention is not particularly limited, and the most suitable size can be selected and used depending on the application and desired properties of the titanium oxide-containing powder. For example, from the viewpoint of placing importance on the high dielectric constant of the titanium oxide-containing powder, larger particles are preferable, and in this case, titanium oxide-containing powder having an average particle size of 10 to 100 μm is preferably used. More preferably, it is 15 to 80 μm, and even more preferably, it is 20 to 60 μm. Furthermore, when the titanium oxide-containing powder is used for small devices, a titanium oxide-containing powder with a smaller particle size is required, and the average particle size is preferably 0.1 to 10 μm, more preferably 0.5 to 8 μm, and even more preferably 1 to 6 μm. The titanium oxide-containing powder of the present invention is in the form of aggregated particles (secondary particles) formed by aggregation of primary particles, and the average particle size of the titanium oxide-containing powder referred to here is the average particle size of the secondary particles. The average particle size of the titanium oxide-containing powder can be measured by the method described in the Examples below.

[0024] The titanium oxide-containing powder of the present invention preferably has a (D90-D10) / D50 in the laser diffraction particle size distribution of 4 or less. By using a material with such a narrow particle size distribution, the composition obtained by blending the powder with a resin has better suitability for thin film formation, and the molded article formed using the composition has higher surface flatness. (D90-D10) / D50 is more preferably 3 or less, and even more preferably 2 or less. The (D90-D10) / D50 value of the titanium oxide-containing powder can be calculated from the D90, D50, and D10 values ​​measured by the method described in the Examples below.

[0025] The titanium oxide-containing powder of the present invention preferably has a circularity of 0.7 or more. Such a high circularity results in excellent filling and dispersibility when the titanium oxide-containing powder is mixed with a resin. The circularity is more preferably 0.75 or more, and even more preferably 0.8 or more. The circularity of the titanium oxide-containing powder can be measured by the method described in the Examples below.

[0026] The titanium oxide-containing powder of the present invention has a high dielectric constant and a low dielectric loss tangent, and is therefore suitable as a dielectric material. When the titanium oxide-containing powder of the present invention is used as a dielectric material, it may be mixed with a resin to form a resin composition. Such a resin composition containing the titanium oxide-containing powder of the present invention and a resin is also one aspect of the present invention. When mixing the titanium oxide-containing powder into the resin material, in order to further improve the mixing uniformity into the resin material, a dispersant may be used in combination within a range that does not impair the dielectric properties of the substrate material, or the titanium oxide-containing powder may be surface-treated with a surface treatment agent selected from an organic surface treatment agent and / or an inorganic surface treatment agent.

[0027] The dispersant is not particularly limited, and any conventionally known dispersant can be used. Examples of dispersants include, but are not limited to, those made of various polymers of fatty acids, fatty acid metal salts, fatty acid esters, and fatty acid amides. Examples of dispersants that can be used include low-molecular or high-molecular dispersants. The amount of the dispersant added to the resin material can be appropriately set depending on the purpose.

[0028] The surface treatment agent for the titanium oxide-containing powder is not particularly limited, and may be appropriately selected depending on the intended application. Examples of the organic surface treatment agent include organosilicon compounds such as silane coupling agents, e.g., hexadimethylsilazane, and organopolysiloxane-based surfactants; organotitanium compounds, e.g., titanium coupling agents; organophosphorus compounds, e.g., phosphate esters; organofluorine compounds, e.g., perfluorocarboxylic acids; fatty acids, e.g., lauric acid, palmitic acid, and stearic acid; polyhydric alcohols, e.g., trimethylolpropane; and alkanolamines, e.g., triethanolamine. Examples of inorganic surface treatment agents include oxoacids (e.g., silicic acid and aluminic acid), metal salts of oxoacids (e.g., sodium silicate and sodium aluminate), oxides, hydroxides, and hydrated oxides of metals such as aluminum, silicon, zirconium, tin, titanium, antimony, zinc, cobalt, and manganese.

[0029] The titanium oxide-containing powder that has been surface-treated with the above-mentioned surface treatment agent has a layer of the surface treatment agent on the surface of the titanium oxide-containing powder. The titanium oxide-containing powder that has been surface-treated with a surface treatment agent may be surface-treated with only one of an organic surface treatment agent and an inorganic surface treatment agent, or may be surface-treated with both. When the titanium oxide-containing powder is surface-treated with both an organic surface treatment agent and an inorganic surface treatment agent, it is preferable that the titanium oxide-containing powder is surface-treated with an inorganic surface treatment agent and then surface-treated with an organic surface treatment agent. In this case, the surface-treated titanium oxide-containing powder has a layer of an inorganic surface treatment agent on the surface of the titanium oxide-containing powder, and has a layer of an organic surface treatment agent thereon.

[0030] 2. Manufacturing method of titanium oxide-containing powder The method for producing a titanium oxide-containing powder of the present invention is characterized by comprising a first step of preparing a slurry containing titanium oxide having an average secondary particle size of 0.1 to 4 μm and a solvent, a second step of obtaining granulated particles from the slurry obtained in the first step, and a third step of firing the particles obtained in the second step at a temperature of 1100° C. or less. In this way, by firing granulated particles of a predetermined size at a predetermined temperature that is relatively low, the resulting titanium oxide-containing powder has a high dielectric constant. Furthermore, the primary particles that make up the granulated particles grow by firing and form necks, which reduces the specific surface area and the dielectric tangent. This makes it possible to produce a titanium oxide-containing powder having particles that have a high dielectric constant and a low dielectric tangent and are suitable for mixing with resin.

[0031] The titanium oxide used as the raw material for preparing the slurry in the first step preferably has an average primary particle size of 0.001 to 1 μm. By using titanium oxide having a small average primary particle size, the titanium oxide-containing powder obtained by the titanium oxide-containing powder production method of the present invention can have a small particle size, and the granulated particles can have regular internal and surface structures. The average primary particle size of titanium oxide is more preferably 0.001 to 0.5 μm, and even more preferably 0.001 to 0.2 μm. The average primary particle size of titanium oxide can be measured by the method described in the Examples below.

[0032] The titanium oxide contained in the slurry prepared in the first step may have an average secondary particle diameter of 0.1 to 4 μm, but in order to make the shape of the titanium oxide-containing powder obtained by the method for producing a titanium oxide-containing powder of the present invention closer to a sphere, the average secondary particle diameter is preferably 0.1 to 3 μm, and more preferably 0.1 to 2 μm. The average particle size of the secondary particles of titanium oxide can be measured by the method described in the Examples below.

[0033] Examples of the solvent used in the first step include water, methanol, ethanol, propanol, etc. Among these, water is preferred.

[0034] The concentration of the slurry prepared in the first step is not particularly limited, but the solid content is preferably 0.5 to 30% by volume. With such a solid content, it becomes easy to obtain granulated particles having an appropriate particle size in the second step, and the shape of the titanium oxide-containing powder obtained can be made closer to a sphere. The solid content of the slurry is more preferably 0.5 to 15% by volume, and even more preferably 1 to 8% by volume.

[0035] The first step may be a step of preparing a slurry containing titanium oxide having an average secondary particle diameter of 0.1 to 4 μm and a solvent, but is preferably a step of preparing a slurry containing titanium oxide having an average secondary particle diameter of 0.1 to 4 μm, a calcium-containing compound, and a solvent. By drying and firing the slurry containing the calcium-containing compound to produce a titanium oxide-containing powder in this way, the titanium oxide-containing powder obtained is a powder containing titanium oxide and calcium titanate, and thus a powder with a superior dielectric constant can be obtained. In addition, by using the calcium-containing compound, the occurrence of dents in the particles obtained by granulating the slurry is suppressed, and thus the titanium oxide-containing powder finally obtained tends to have a spherical particle shape. In addition, the firing temperature can be lowered, thereby suppressing the aggregation of the granulated particles during firing. As a result, the obtained powder has excellent filling properties and dispersibility when mixed with a resin.

[0036] When a calcium-containing compound is used in the first step, the calcium-containing compound to be used is not particularly limited, and various compounds containing calcium element can be used, among which a compound that is partially or entirely water-soluble is preferred. In addition, when a partially water-soluble compound or a water-insoluble compound is mixed in the slurry as solid particles, it is preferred to use one having an average primary particle size of 1 μm or less. Examples of calcium-containing compounds include calcium carbonate, calcium acetate, calcium nitrate, calcium oxalate, calcium hydrogen carbonate, calcium titanate, etc., and one or more of these can be used. Among these, calcium-containing compounds such as calcium carbonate and calcium acetate are preferred. In particular, when water-soluble calcium acetate is used, it is reprecipitated during spray drying, resulting in more uniform mixing, and the titanium oxide-containing powder obtained by the production method of the present invention is more likely to become spherical particles with a more uniform internal structure, resulting in excellent dielectric properties.

[0037] When a calcium-containing compound is used in the first step, the amount of the calcium-containing compound used is preferably such that the amount of calcium element contained in the calcium-containing compound is 0.6 to 83 mol% relative to 100 mol% of titanium element contained in the titanium oxide used in the first step. By using the calcium-containing compound in such a ratio, the titanium oxide-containing powder obtained by the production method of the present invention has better dielectric properties. More preferably, the amount of calcium element contained in the calcium-containing compound is 1.4 to 57 mol%, even more preferably, the amount of calcium element is 2.9 to 46 mol%, and particularly preferably, the amount of calcium element is 2.9 to 23 mol%, relative to 100 mol% of titanium element contained in the titanium oxide used in the first step.

[0038] In the first step, other components may be used in addition to titanium oxide, a solvent, and a calcium-containing compound. Examples of other components include dispersants such as ammonium polyacrylate and polyvinyl alcohol, and binders. One or more of these may be used. In particular, the average primary particle diameter of titanium oxide is 0.1 μm or more, and the specific surface area is 20 m 2 When the binder is used, the strength of the granulated particles obtained in the second step can be increased, and it becomes possible to granulate relatively large titanium oxide particles that are difficult to granulate.

[0039] The amount of the dispersant used in the first step is preferably 0 to 6 mass % relative to 100 mass % of the titanium oxide used in the first step, more preferably 0 to 5 mass %, and even more preferably 0 to 4 mass %.

[0040] The amount of the binder used in the first step is preferably 0 to 4 mass % relative to 100 mass % of the titanium oxide used in the first step, more preferably 0 to 3 mass %, and even more preferably 0 to 2 mass %.

[0041] In the first step, the method for preparing a slurry by mixing titanium oxide with a solvent and other raw materials in a solvent is not particularly limited, and may be performed using any method such as a ribbon mixer, a Spartan mixer, a planetary ball mill, a bead mill, etc. When using a planetary ball mill or a bead mill, examples of the media to be used include glass beads, alumina beads, zirconia beads, titania beads, silicon nitride beads, agate beads, tungsten carbide beads, etc.

[0042] The second step is a granulation step for obtaining granulated particles from the slurry obtained in the first step. In the first step, a slurry containing titanium oxide of an appropriate size is prepared, and granulation is performed using the slurry to obtain granulated particles of an appropriate size composed of primary particles. Since the aggregation between the granulated particles during the firing in the third step can be suppressed, a powder of a particle size suitable for mixing with a resin can be obtained without performing a step of crushing the particles. Furthermore, when the granulated particles composed of such primary particles are fired in the third step, the synthesis temperature of calcium titanate is lowered when a calcium-containing compound is used in the first step, so that calcium titanate can be sufficiently synthesized even by firing at a low temperature in the third step.

[0043] In the second step, the method of obtaining granulated particles is not particularly limited as long as granulated particles can be obtained from the slurry obtained in the first step. In addition to granulation by spray drying, wet granulation such as extrusion granulation, stirring granulation, fluidized bed granulation, and rolling granulation, and dry granulation in which powder is compressed and molded can be used. Among these, a method of drying the slurry by spray drying to obtain granulated particles is preferred. When spray drying is used, the composition of the composite powder containing titanium oxide and other components can be easily changed by changing the raw material of the slurry. When granulation by spray drying is performed, it is preferable to use a four-fluid nozzle type micromist spray dryer to obtain fine granulated particles of several microns.

[0044] The average particle size of the granulated particles obtained by granulating the slurry in the second step is not particularly limited and may be appropriately selected depending on the application of the titanium oxide-containing powder to be produced, but is preferably 100 μm or less. The average particle size of the granulated particles obtained in the second step is usually 0.1 μm or more. By firing the granulated particles having such an average particle size in the third step, a titanium oxide mixed powder having a particle size suitable for mixing with a resin can be obtained. From the viewpoint of emphasizing a high dielectric constant of the titanium oxide-containing powder produced, the average particle size of the granulated particles obtained in the second step is more preferably 15 to 80 μm, and further preferably 20 to 60 μm. When the produced titanium oxide-containing powder is used for small device applications, the average particle size of the granulated particles obtained in the second step is more preferably 0.1 to 10 μm, even more preferably 0.5 to 8 μm, and most preferably 1 to 6 μm. The average particle size of the granulated particles can be measured by the method described in the Examples below.

[0045] The third step is a step of firing the granulated particles obtained in the second step at a temperature of 1100°C or less. When the granulated particles composed of the primary particles obtained in the second step are fired at such a temperature, the primary particles constituting the granulated particles grow and form necks, which reduces the specific surface area of ​​the granulated particles and reduces the dielectric tangent. The granulated particles obtained in the second step are easily necked even by firing at a low temperature in the third step because the primary particles in the granulated particles are closely adjacent to each other, while necks are not easily formed between adjacent granulated particles and the granulated particles are not easily aggregated with each other, so that a powder containing dispersed granulated particles can be obtained without performing a step of crushing the particles. Although the step of crushing the particles deteriorates the dielectric properties of the particles, the manufacturing method of the present invention can obtain a powder with a small particle size without performing a step of crushing the particles, so that a titanium oxide-containing powder having excellent dielectric properties while having a particle size suitable for mixing with a resin can be obtained. In addition, by firing the granulated particles obtained in the second step at such a relatively low temperature, the particles of the titanium oxide-containing powder obtained are not too hard. This prevents the inner walls and stirring screw of the mixing device from being scraped or damaged when the titanium oxide-containing powder and resin are mixed together, and prevents wear on parts caused by particles and the resulting introduction of foreign matter. The temperature for firing the particles may be 1100° C. or lower, and is preferably 800 to 1050° C., more preferably 900 to 1000° C., and even more preferably 950 to 1000° C. The firing temperature here means the maximum temperature during firing. The firing time is preferably 0.5 to 8 hours, more preferably 1 to 7 hours, and even more preferably 2 to 6 hours. The firing time here means the holding time at the maximum temperature during firing.

[0046] The heating rate during firing in the third step is not particularly limited and may be appropriately set depending on the size of the firing furnace, the amount of granulated particles to be fired, etc., but is preferably 50 to 300° C. / h, more preferably 50 to 200° C. / h, and even more preferably 50 to 100° C. / h. The temperature drop rate is also preferably the same as the temperature rise rate.

[0047] The method for producing a titanium oxide-containing powder of the present invention may include other steps as long as it includes the above steps 1 to 3. Examples of the other steps include a step of removing beads after mixing when the raw materials are mixed using a bead mill in the first step, and a step of classifying the raw materials by sieving. EXAMPLES

[0048] In order to explain the present invention in detail, specific examples are given below, but the present invention is not limited to these examples. Unless otherwise specified, "%" and "wt%" mean "weight % (mass %)". The measurement methods for each physical property are as follows.

[0049] <Specific surface area> The specific surface area was measured by the BET single point method using a Mountech Macsorb HM-1220. Pretreatment was performed at 130°C for 15 minutes under a stream of pure nitrogen gas, and measurements were performed using a mixture of 70% helium and 30% nitrogen as the carrier gas. <Average primary particle diameter> The specific surface area was measured by the BET single point method using Macsorb HM-1220 manufactured by Mountech Co., Ltd., and the average primary particle size was calculated. Pretreatment was performed at 200°C for 30 minutes under a pure nitrogen gas flow, and measurements were performed using a mixed gas of 70% helium and 30% nitrogen as the carrier gas. D=6 / (ρ·Sm) D: Average primary particle diameter [μm] ρ: True density [g / cm 3 ] Sm: Specific surface area [m 2 / g] <Average diameter of secondary particles> The average particle size of secondary particles was measured using a Microtrac-Bell MT3300II. The powder to be measured was placed in a bath filled with an aqueous solution of sodium hexametaphosphate with a concentration of 0.0025% by mass, and dispersed into a dispersed slurry by ultrasonic dispersion in the same device at an output of 40 W for 120 seconds. The particle refractive index was 2.72, the solvent refractive index was 1.333, and measurements were made on a volume basis. The median diameter (D50) obtained here was taken as the average particle diameter of the secondary particles. <Particle size distribution of granulated particles> The particle size distribution of the granulated particles was measured using a Microtrac Bell MT3300II. The powder to be measured was placed in a bath filled with an aqueous solution of sodium hexametaphosphate with a concentration of 0.0025% by mass, and dispersed into a dispersed slurry by ultrasonic dispersion in the same device at an output of 40 W for 120 seconds. The particle refractive index was 2.72, the solvent refractive index was 1.333, and measurements were performed on a volume basis. From the particle size distribution measurement results obtained here, the respective cumulative frequencies D10, D50, and D90 were calculated. <Dielectric constant ε·Dielectric tangent tanδ> The dielectric constant ε and dielectric tangent tanδ were measured using a measuring device consisting of a powder cavity resonator (manufactured by AET) connected to a vector network analyzer P9373B (manufactured by Keysight). The powder to be measured was packed into a quartz tube so that the bulk density was approximately 1.0, and measurements were performed at a frequency of 10 GHz. <SEM、SEM-EDS> SEM observation and SEM-EDS measurement were performed using a JEOL JSM-6510A. The measurement samples were platinum-coated in advance using a JEOL JEC-3000FC auto-fine coater. <xrd> X-ray diffraction was measured using a Rigaku MiniFlex 600-C. The measurement conditions were 1D scan, 10-90°, measurement step width 0.01°, measurement speed 20.0° / min, no spin, tube voltage 40kV, tube current 15mA. The powder was ground in an agate mortar before measurement. <Calcium titanate content> The Ti and Ca content was measured using a Rigaku Corporation X-ray fluorescence spectrometer ZSX PrimusII. The measurement application was EZ scan, the measurement conditions were vacuum atmosphere, measurement diameter 30 mm, measurement time standard, and the measurement powder sample was molded into a Φ35 mm pellet. The calcium titanate content was calculated from the obtained measurements. <Circularity> The circularity was determined as the average value of the circularity obtained by analyzing 100 or more particles using the SEM image measured by the above method with AI image analysis software DeepCle manufactured by Sakai Chemical Industry Co., Ltd. The image analysis model used was AI model: 4.3201_2f_r. As analytical examples, the analytical results of the titanium oxide mixed powder of Example 11 and the titanium oxide mixed powder of Comparative Example 3 are shown in Tables 1 and 2, respectively.

[0050] [Table 1]

[0051] [Table 2]

[0052] Example 1 1.6g of ammonium polyacrylate (Kao Corporation, Poise 532A) was added to 780.9g of pure water, and 72.5g of titanium dioxide (Sakai Chemical Industry Co., Ltd., STR-100N, average primary particle size 0.015μm) and 5.3g of calcium carbonate (Sakai Chemical Industry Co., Ltd., CWS-20, average primary particle size 0.1μm) were added. This was pulverized and mixed in a bead mill, and the resulting slurry was passed through a sieve (Tokyo Screen Co., Ltd., test sieve, mesh size 25μm) to remove the beads. The collected slurry was diluted twice with the same volume of pure water to obtain a slurry with a solid concentration of 1.2vol%. The average particle size of the titanium dioxide secondary particles in the resulting slurry was 0.5μm. The obtained slurry was granulated using a spray dryer (GF Micromist Spray Dryer MDL-050CM) to produce a mixed granulated powder of titanium dioxide and calcium carbonate. The resulting mixed granulated powder was fired in an electric furnace at a heating rate of 100°C / h and held at 950°C for 2 hours to obtain the desired titanium oxide-containing powder (composite granulated powder of titanium dioxide and calcium titanate). The titanium oxide-containing powder thus obtained had an average particle size of 4.3 μm, a dielectric constant of 18.9 at 10 GHz, and a dielectric loss tangent of 0.0030. The specific surface area was 7.6 m 2 / g. The particle size distribution measurement results of the obtained titanium oxide-containing powder are shown in Figure 3, and a photograph of the SEM observation results is shown in Figure 4. In addition, a photograph of the SEM-EDS measurement results is shown in Figure 5-1, and an analysis spectrum is shown in Figure 5-2. Furthermore, the XRD measurement results of the obtained titanium oxide-containing powder are shown in Figure 6. It was confirmed from Figures 5-1 and 5-2 that the titanium oxide-containing powder obtained was a composite granulated powder of titanium dioxide and calcium titanate. Also, it was confirmed from Figure 6 that the titanium oxide-containing powder obtained was composed of titanium dioxide and calcium titanate crystals.

[0053] Examples 2 to 7 A titanium oxide-containing powder was obtained in the same manner as in Example 1, except that the particle sizes and amounts of titanium dioxide and calcium carbonate used, and the firing temperature were changed as shown in Table 3. The dielectric constant, dielectric tangent, and specific surface area at 10 GHz of the obtained titanium oxide-containing powder are shown in Table 3.

[0054] Example 8 1.6 g of ammonium polyacrylate (Kao Corporation, Poise 532A) was added to 781 g of pure water, and 72.0 g of titanium dioxide (Sakai Chemical Industry Co., Ltd., STR-100N, average primary particle size 0.015 μm) and 7.6 g of calcium titanate (Sakai Chemical Industry Co., Ltd., CT-03, average primary particle size 0.3 μm) were added. This was pulverized and mixed in a bead mill, and the resulting slurry was passed through a sieve (Tokyo Screen Co., Ltd., test sieve, mesh size 25 μm) to remove the beads. The collected slurry was diluted twice with the same volume of pure water to obtain a slurry with a solid concentration of 1.2 vol%. The average particle size of the titanium dioxide secondary particles in the resulting slurry was 0.5 μm. The obtained slurry was granulated using a spray dryer (GF Micromist Spray Dryer MDL-050CM) to produce a mixed granulated powder of titanium dioxide and calcium titanate. The resulting mixed granulated powder was fired in an electric furnace at a heating rate of 100°C / h and held at 950°C for 2 hours to obtain the desired titanium oxide-containing powder (composite granulated powder of titanium dioxide and calcium titanate). The titanium oxide-containing powder thus obtained had an average particle size of 3.0 μm, a dielectric constant of 14.6 at 10 GHz, and a dielectric loss tangent of 0.0050. The specific surface area was 13.4 m 2 / g.

[0055] Examples 9 and 10 A titanium oxide-containing powder was obtained in the same manner as in Example 8, except that the particle sizes and amounts of titanium dioxide and calcium titanate used, and the firing temperature were changed as shown in Table 3. The dielectric constant, dielectric tangent, and specific surface area at 10 GHz of the obtained titanium oxide-containing powder are shown in Table 3.

[0056] Example 11 1.6g of ammonium polyacrylate (Kao Corporation, Poise 532A) was added to 652.6g of pure water, and 80g of titanium dioxide (Sakai Chemical Industry Co., Ltd., STR-100N, average primary particle size 0.015μm) and 10.3g of calcium acetate monohydrate (Kishida Chemical Co., Ltd.) were added. This was pulverized and mixed in a bead mill, and the resulting slurry was passed through a sieve (Tokyo Screen Co., Ltd., test sieve, mesh size 25μm) to remove the beads. The collected slurry was diluted twice with the same volume of pure water to obtain a slurry with a solid concentration of 1.2vol%. The average particle size of the titanium dioxide secondary particles in the resulting slurry was 0.5μm. The obtained slurry was granulated using a spray dryer (Micromist Spray Dryer MDL-050CM, manufactured by GF Corporation) to obtain a granulated powder mixture of titanium dioxide and calcium acetate. The resulting mixed granulated powder was fired in an electric furnace at a heating rate of 100°C / h and held at 950°C for 4 hours to obtain the desired titanium oxide-containing powder (composite granulated powder of titanium dioxide and calcium titanate). The resulting titanium oxide-containing powder had an average particle size of 5.1 μm, a dielectric constant of 23.5 at 10 GHz, and a dielectric dissipation factor of 0.0032. The specific surface area was 7.2 m 2 / g. The particle size distribution measurement results of the obtained titanium oxide-containing powder are shown in Figure 7, and a photograph of the SEM observation results is shown in Figure 8. Furthermore, a photograph of the SEM-EDS measurement results of the obtained titanium oxide-containing powder is shown in Figure 9-1, and an analysis spectrum is shown in Figure 9-2. Furthermore, the XRD measurement results of the obtained titanium oxide-containing powder are shown in Figure 10. It was confirmed from Figures 9-1 and 9-2 that the titanium oxide-containing powder obtained was a composite granulated powder of titanium dioxide and calcium titanate. Also, it was confirmed from Figure 10 that the titanium oxide-containing powder obtained was composed of titanium dioxide and calcium titanate crystals.

[0057] Examples 12 and 13 A titanium oxide-containing powder was obtained in the same manner as in Example 11, except that the amounts of titanium dioxide and calcium acetate used were changed as shown in Table 3. The dielectric constant, dielectric tangent, and specific surface area at 10 GHz of the obtained titanium oxide-containing powder are shown in Table 3.

[0058] Example 14 400 g of titanium dioxide (manufactured by Sakai Chemical Industry Co., Ltd., STR-100N, average primary particle size 0.015 μm) was added to 3905 g of pure water. This was thoroughly stirred with a stirrer, and the resulting slurry was passed through a sieve (manufactured by Tokyo Screen Co., Ltd., test sieve, mesh size 150 μm) to remove coarse particles, yielding a 2.4 vol% slurry. The average particle size of the titanium dioxide secondary particles in the resulting slurry was 2.0 μm. The obtained slurry was granulated using a spray dryer (Okawara Kakoki Co., Ltd., spray bag dryer, BDP-22E, M-type pin disc, disc rotation speed 20,000 rpm) to obtain a granulated titanium dioxide powder. The obtained granules were fired in an electric furnace under conditions of a temperature rise rate of 100° C. / h and a holding temperature of 900° C. for 2 hours to obtain the desired titanium oxide-containing powder (granulated titanium oxide powder). The titanium oxide-containing powder thus obtained had an average particle size of 23.1 μm, a dielectric constant of 17.1 at 10 GHz, and a dielectric loss tangent of 0.0021. The specific surface area was 6.3 m 2 / g.

[0059] Example 15 A titanium oxide-containing powder was obtained in the same manner as in Example 14, except that the amount of titanium dioxide used was changed as shown in Table 3. The dielectric constant, dielectric tangent, and specific surface area at 10 GHz of the obtained titanium oxide-containing powder are shown in Table 3.

[0060] Example 16 1.5g of ammonium polyacrylate (Kao Corporation, Poise 532A) was added to 780.8g of pure water, and 67.7g of titanium dioxide (Sakai Chemical Industry Co., Ltd., SSP-N, average primary particle size 0.006μm) and 5.0g of calcium carbonate (Sakai Chemical Industry Co., Ltd., CWS-20, average primary particle size 0.1μm) were added. This was pulverized and mixed in a bead mill, and the resulting slurry was passed through a sieve (Tokyo Screen Co., Ltd., test sieve, mesh size 25μm) to remove the beads. The collected slurry was diluted twice with the same volume of pure water to obtain a slurry with a solid concentration of 1.2vol%. The average particle size of the titanium dioxide secondary particles in the resulting slurry was 0.6μm. The obtained slurry was granulated using a spray dryer (GF Micromist Spray Dryer MDL-050CM) to produce a mixed granulated powder of titanium dioxide and calcium carbonate. The resulting mixed granulated powder was fired in an electric furnace at a heating rate of 100°C / h and held at 950°C for 4 hours to obtain the desired titanium oxide-containing powder (composite granulated powder of titanium dioxide and calcium titanate). The titanium oxide-containing powder thus obtained had an average particle size of 4.8 μm, a dielectric constant of 26.5 at 10 GHz, and a dielectric loss tangent of 0.0043. The specific surface area was 4.4 m 2 / g.

[0061] Comparative Example 1 1 g of anatase-type titanium oxide (manufactured by Sakai Chemical Industry Co., Ltd., product name "SSP-25", average primary particle size 0.006 μm) was calcined at 1000° C. for 4 hours. The titanium oxide powder thus obtained had an average particle size of 3.2 μm, a dielectric constant of 10.7 at 10 GHz, and a dielectric loss tangent of 0.0033. The specific surface area was 3.7 m 2 / g.

[0062] Comparative Example 2 A titanium oxide-containing powder (a composite granulated powder of titanium dioxide and calcium titanate) was obtained in the same manner as in Examples 6 and 7, except that the firing temperature was changed as shown in Table 3. The titanium oxide-containing powder thus obtained had an average particle size of 6.6 μm, a dielectric constant of 22.3 at 10 GHz, and a dielectric loss tangent of 0.0024. The specific surface area was 3.3 m 2 / g.

[0063] Comparative Example 3 200g of titanium dioxide (Sakai Chemical Industry Co., Ltd., SSP-N, average primary particle size 0.006μm) and 25.8g of calcium acetate monohydrate (Kishida Chemical Co., Ltd.) were added to 952.4g of pure water. This was mixed using a disper, and the resulting slurry was passed through a sieve (Tokyo Screen Co., Ltd., test sieve, mesh size 25μm) to obtain a slurry with a solid concentration of 4.8vol%. The average particle size of the titanium dioxide secondary particles in the resulting slurry was 1.3μm. The resulting slurry was left to stand in a dryer to dry, yielding a titanium dioxide / calcium acetate mixed powder. The resulting mixed powder was crushed in a mortar and then fired in an electric furnace at a heating rate of 100°C / h and held at 950°C for 2 hours, yielding a titanium dioxide / calcium titanate mixed powder. The resulting titanium dioxide-containing powder had an average particle size of 3.8 μm, a dielectric constant of 17.4 at 10 GHz, and a dielectric dissipation factor of 0.0050. The specific surface area was also 3.8 m 2 / g.

[0064] [Table 3]

[0065] The results in Table 3 confirm that by using the method for producing a titanium oxide-containing powder of the present invention, it is possible to obtain a titanium oxide-containing powder that has excellent dielectric properties, i.e., a high dielectric constant and a low dielectric tangent, and also has a specific surface area that is suitable for mixing with a resin material.< / xrd>

Claims

1. A powder containing titanium oxide, The powder has a dielectric constant of 14 or more at 10 GHz, a dielectric dissipation factor of 0.006 or less, and a specific surface area of ​​4 to 16 m 2 / g.

2. The titanium oxide-containing powder according to claim 1, further comprising calcium titanate.

3. 2. The titanium oxide-containing powder according to claim 1, characterized in that the average particle size is 0.1 to 100 μm.

4. A resin composition comprising the titanium oxide-containing powder according to any one of claims 1 to 3 and a resin.

5. A method for producing a titanium oxide-containing powder, comprising the steps of: The production method includes a first step of preparing a slurry containing titanium oxide having an average secondary particle diameter of 0.1 to 4 μm and a solvent; A second step of obtaining granulated particles from the slurry obtained in the first step; and a third step of sintering the particles obtained in the second step at a temperature of 1100° C. or less.

2. The method for producing a titanium oxide-containing powder comprising the steps of:

6. 6. The method for producing a titanium oxide-containing powder according to claim 5, wherein the first step is a step of preparing a slurry containing titanium oxide having an average secondary particle diameter of 0.1 to 4 μm, a calcium-containing compound, and a solvent.

7. 7. The method for producing a titanium oxide-containing powder according to claim 6, wherein the calcium-containing compound is at least one selected from the group consisting of calcium carbonate, calcium acetate, calcium nitrate, calcium oxalate, calcium bicarbonate, and calcium titanate.

8. 6. The method for producing a titanium oxide-containing powder according to claim 5, wherein the second step is carried out by spray-drying the slurry.

Citation Information

Patent Citations

  • Optical separator

    JP1982027224A

  • Dielectric ceramic powder, manufacturing method of dielectric ceramic powder, and compound dielectric material

    JP2005174711A